Effects of Alkaline Pretreatment on the Characteristics of Collagen from Mangrove Conch (Telescopium telescopium) - Sri Purwaningsih; Riyan Triono (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
The horn snail (Telescopium telescopium) is a gastropod living in mangrove forests and is considered as a pond pest. This study was aimed to determine the effects of alkaline and acetic acid pretreatment on the characteristics of collagen from the horn snail meat. The immersion of the meat in NaOH 0.20% for 10 hours gave a significant reduction in non-collagen protein content (α = 0.05). Further immersion with acetic acid 0.05% for 6 hours also significantly affected (α = 0.05) the swelling degree and the collagen solubility. The extraction yield was 1.08±0.21%, with 72.23% of brightness, and the viscosity was 16.34 cP. The proline content of the collagen was 9.21%.